Temperaturen des Begehrens als konventionelle Metaphern im Hard-Core-Liebesroman - Pokrywka, Rafał (Studia Germanica Posnaniensia, 2015)
The paper focuses upon the latest adult romance novels that appeared after Fifty Shades of Grey, anal-yses their stylistic dimensions and argues with the essay Hard-Core Romance by Eva Illouz. At first the genre is defined, above all on the basis of its medial presence (chapter 1. Genre). Furthermore tempera-ture metaphors in two representative texts of the genre (E.L. James Fifty Shades of Grey and Sylvia Day Bared to You) are analyzed as stylistic (chapter 2. Conventional Temperature Metaphors) as well as rhetorical artifacts (chapter 3. Rhetoric of Metaphor). In conclusion the question of language in the novels and its usefulness in the task described by Illouz is raised (chapter 4. A New Love Order?). The new adult romance novel seems to be a conventional cultural text of little rhetorical power, thus unable to carry important social ideas.